The librarianist : a novel [large type] - deWitt, Patrick, 1975- (Harper Large Print, an imprint of HarperCollinsPublishers, 2023)
"Bob Comet is a retired librarian, isolated but not lonely, living out his quiet days in a mint-colored house in Oregon...One morning, out on his daily walk, he performs an act of kindness that brings him into contact with a nearby senior center, where he soon begins volunteering. Here, as a community of peers and friends gathers around Bob,... the events of his life and the details of his character are revealed. Behind Bob Comet's plain facade is the story of an unhappy child's runaway adventure, of true love found and stolen away, of the purpose and pride found in vocation, and the ultimate acceptance of a life lived to the side of the masses"--